Women and interreligious dialogue - Cornille, C. (Catherine); Maxey, Jillian (2013)
"Though women have been objects more often than subjects of interreligious dialogue, they have nevertheless contributed in significant ways to the dialogue, just as the dialogue has also contributed to their own self-understanding. This volume, the fifth in the Interreligious Dialogue Series, brings together historical, critical, and constructive approaches to the role of women in the dialogue between religions. These approaches deal with concrete examples of women's involvement in dialogue, critical reflections on the representation of women in dialogue, and the important question of what women might bring to the dialogue. Together, they open up new avenues for reflection on the nature and purpose of interreligious dialogue." -- Publisher's description.
Includes bibliographical references.
Keywords: Women and religion; Multiculturalism -- Religious aspects; Religion -- Relations; Religious pluralism; Dialogue -- Religious aspects